Design of lightweight buffer-free sram and robust ring oscillator based physical unclonable functions - Liu, Chaoqun (2018)
In the era of internet of things, electronic devices are becoming ubiquitous. To perform secure tasks such as identification and authentication, security modules need to be embedded in such devices. Physical unclonable function (PUF) is an emerging security primitive to address vulnerability of the traditional data protection scheme that stores the secret keys in non-volatile memories. Despite various kinds of PUFs proposed so far, this dissertation investigates two most popular PUFs, which are Static Random Access Memory (SRAM) and Ring oscillator (RO) based PUFs. SRAM has recently been developed into a PUF for generating chip-unique signatures for hardware cryptography. The most compelling issue in designing a good SRAM-based PUF (SPUF) is that while maximizing the mismatches between the transistors in the cross-coupled inverters to improve the quality of SPUF, this process itself gives rise to increased memory read/write failures. For this reason, the memory cells of existing SPUFs cannot be reused as storage elements, which increases the overheads of cryptographic system where long signatures and high-density storage are both required. This thesis presents a novel design methodology for dual-mode SRAM cell optimization. The design conflicts are resolved by using word-line voltage modulation, dynamic voltage scaling, negative bit-line and adaptive body bias tech- niques to compensate for reliability degradation due to transistor downsizing. The augmented circuit-level techniques expand the design space to achieve a good solution to fulfill several otherwise contradicting key design qualities for both modes of operation, as evinced by the statistical analysis and simulation results based on complementary metal–oxide–semiconductor (CMOS) 45 nm bulk Predictive Technology Model. Using power-up reset to reuse SRAM as PUF suffers from two major constraints. First, it has limited entropy of only one response bit per cell. Second, as power-up reset has a global effect, extra storage is needed to temporarily buffer the original SRAM content before switching to PUF mode. This process has introduced extra area-power overhead as well as potential security leakage. The emerging dual-port (DP) SRAM cell offers attractive multiple access capability for low-power and high-speed memory transfer. By leveraging the forbidden contention state in one of its four multiple access modes, a new DP-SRAM based PUF is proposed to generate two independent response bits per cell and limit data buffering to only those cell content addressed by the challenge. Simulation results based on PTM 22nm LP CMOS model has corroborated its superior reliability, uniqueness and randomness. RO based PUF is an emerging hardware security primitive but its response reproducibility is susceptible to changes in operating conditions and device aging. Present solutions to increase RO PUF reliability either incur large hardware overhead or require sophisticated RO selection algorithm. This research exploits the optimal biasing of current starved (CS) inverter for the design of RO PUF with very high reliability against both temperature and voltage variations. With two additional transistors, the CS inverter can be adaptively biased at idle time and in active mode to significantly reduce the overall stress, making the proposed CS RO PUF robust against both environmental condition variations and aging. Without using error correction code, the reliability is further improved by a low-cost proximity detector circuit with a small sacrifice on challenge-response-pair (CRP) space. The correlation between successive RO pairs of different input challenges is also broken by an irregular clocking of the linear feedback shift register used to encipher the input challenges. Based on Monte Carlo simulation in TSMC 40nm CMOS process, the reliability of native PUF responses has been raised substantially from 89.78% for the regular RO PUF to 95.88% for the proposed CS RO PUF over a broad temperature range of -40 to 120◦C and ± 20% supply variation. With the proximity detector, the proposed Aging-resistant Current-starved RO (ACRO) PUF can attain 100% reliability statistically by discarding 34.47% fewer challenge-response pairs than the regular RO PUF. It is also ∼3.7x more aging resilient than existing aging-resilient RO PUFs with ∼2.38x lower power dissipation.